To determine whether the function \( f(x) = x^3 + 5x + 1 \) is an even function, we need to check if \( f(-x) = f(x) \) for all \( x \).
-
Calculate \( f(-x) \): \[ f(-x) = (-x)^3 + 5(-x) + 1 = -x^3 - 5x + 1 \]
-
Check if \( f(-x) \) is equal to \( f(x) \): \[ f(x) = x^3 + 5x + 1 \] Since \( f(-x) \neq f(x) \), the function is NOT even.
-
Check if \( f(-x) \) equals \( -f(x) \): \[ -f(x) = -(x^3 + 5x + 1) = -x^3 - 5x - 1 \] We can see that \( f(-x) \neq -f(x) \) as well.
Based on this analysis, the statement that best describes the process of determining whether \( f(x) \) is an even function is:
"Determine whether \( (-x)^3 + 5(-x) + 1 \) is equivalent to \( x^3 + 5x + 1 \)."
This checks whether \( f(-x) \) equals \( f(x) \), which is the definition of an even function.